Origami architecture : papercraft models of the world's most famous buildings - Yee, 1968- (North Clarendon, Vt. : Tuttle Pub., 2011)
"CD ROM with templates for cutting Folds flat!"--
"With this book, some card stock paper, and a hobby knife, you can build spectacular recreations of the most famous buildings in the world. It gives instructions and templates for 16 buildings, including the Parthenon, the White House, the Eiffel Tower, the Chrysler building, and the Forbidden City. There are over 900 photographs detailing the cutting and assembling of the pieces without using glue or tape, except for attaching it to its base. Once the structure is attached to the base not only will it look amazing, but it can be folded up and taken anywhere. For the would be architect, the papercraft hobbyist, or a model builder, Origami Architecture will provide hours of activity and an impressive result"--
Machine generated contents note : buildings --Lincoln Memorial --Westminster Abbey --US Capitol building --Parthenon --White House --Osaka Castle --National Opera House in China --Eiffel Tower --London Bridge --The Forbidden City --Arc d'Triomphe --Leaning Tower of Pisa --Sydney Opera House --Chrysler Building --Petronas Towers.
Keywords: Origami; Architectural models; Cut-out craft; Paper art